Upaya Pembangunan Pendidikan, Sosial, dan Ekonomi di Indonesia: Apa Kontribusi Muhammadiyah? - Harun Alrasyid; Ramlianto Ramlianto; Abdul Malik (Program Pascasarjana IAIN Langsa, 2025)
Despite the extensive discussion of Islamic organizations in Indonesia, existing studies tend to examine Muhammadiyah’s role in education, social services, or economic activities in a fragmented manner, without providing an integrated analysis of its contributions to national development. This gap highlights the need for a comprehensive examination of Muhammadiyah’s multifaceted role in educational, social, and economic development. Accordingly, this research aims to analyze Muhammadiyah’s contributions to these three sectors and to assess its significance as an agent of social change in Indonesia. This study employs a qualitative research design using a literature review approach, drawing on books, academic journals, organizational reports, and other relevant scholarly sources. The findings reveal that Muhammadiyah has made substantial contributions to the development of a modern and inclusive education system through its extensive network of educational institutions, while also strengthening social resilience through community empowerment programs, health services, and humanitarian initiatives. In the economic sphere, Muhammadiyah promotes sharia-based entrepreneurship and supports the development of micro, small, and medium enterprises, thereby fostering economic independence. These findings suggest that Muhammadiyah’s adaptive strategies and commitment to Islamic values enable it to remain responsive to contemporary challenges. This study implies that Muhammadiyah’s integrated approach to education, social welfare, and economic development can serve as a strategic model for strengthening the role of civil society organizations in supporting sustainable national development.